2013
DOI: 10.4161/cib.22279
|View full text |Cite
|
Sign up to set email alerts
|

Dim scotopic illumination accelerates the reentrainment following simulated jetlags in a diurnal experimental model, Drosophila

Abstract: Jetlag results from the misalignment between the endogenous circadian timing and the civil timing after a transmeridian flight. Efficacy of the dim nocturnal illumination (0.03 lx) in accelerating the reentrainment following simulated jetlags in Drosophila biarmipes was examined by subjecting the flies to 24 h light-dark cycles in which the 12 h photophase was at 300 lx for all flies but the scotophase was at 0 and 0.03 lx for the control and experimental flies, respectively. Reentrainment was always faster in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The flies in that study appeared to have a dim light preference and did not simply become active for more hours a day but shifted their initiation of activity from the morning period (M) to the evening period (E). In another species of fruit fly, Drosophila ( Sophophora ) biarmipes , dim light (0.03 lx) at night sped up re-entraintment (recovery of normal circadian pattern) after rhythm disruption more effectively than did total darkness [ 81 ]. Similar effects of dim lighting have been observed in Syrian hamsters ( Mesocricetus auratus ), where nocturnal illumination of 0.004 lx (equivalent to dim moonlight) was sufficient to accelerate re-entrainment relative to total darkness after disruption of circadian cycles [ 82 ], demonstrating that even small amounts of light during scotophase can alter periodic locomotor rhythms, when compared to what occurs in studies that employ total darkness as a control treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flies in that study appeared to have a dim light preference and did not simply become active for more hours a day but shifted their initiation of activity from the morning period (M) to the evening period (E). In another species of fruit fly, Drosophila ( Sophophora ) biarmipes , dim light (0.03 lx) at night sped up re-entraintment (recovery of normal circadian pattern) after rhythm disruption more effectively than did total darkness [ 81 ]. Similar effects of dim lighting have been observed in Syrian hamsters ( Mesocricetus auratus ), where nocturnal illumination of 0.004 lx (equivalent to dim moonlight) was sufficient to accelerate re-entrainment relative to total darkness after disruption of circadian cycles [ 82 ], demonstrating that even small amounts of light during scotophase can alter periodic locomotor rhythms, when compared to what occurs in studies that employ total darkness as a control treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of dim lighting have been observed in Syrian hamsters ( Mesocricetus auratus ), where nocturnal illumination of 0.004 lx (equivalent to dim moonlight) was sufficient to accelerate re-entrainment relative to total darkness after disruption of circadian cycles [ 82 ], demonstrating that even small amounts of light during scotophase can alter periodic locomotor rhythms, when compared to what occurs in studies that employ total darkness as a control treatment. It has been suggested that such an effect might be caused by dim lighting disrupting the coupling between the M and E oscillators [ 81 ], though data for mice ( Mus musculus ) at least indicate that this effect is mediated by clock genes outside the SCN [ 83 ]. Regardless of the mechanism, dALAN is able to alter periodic locomotor behavior in multiple species of fruit flies and in mammals.…”
Section: Discussionmentioning
confidence: 99%